2018
DOI: 10.1177/1045389x18798949
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of piezoelectric active repair of edge-cracked plate

Abstract: This article proposes an alternative model for active repair for an edge-cracked plate with adhesively bonded piezoelectric actuator. It computes the Mode-I stress intensity factor (SIF) produced by the piezoelectric actuators using appropriate derived geometrical weight functions. Furthermore, this article presents an experimental study to verify the proposed analytical model and the finite element analysis using ANSYS software. Therefore, the analytical, finite element and experimental results for Mode-I ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The ideas were developed to produce compression/tension stress around the damaged area along with the width of the piezoelectric actuator. The authors stated that increasing the piezoelectric voltage will result in a decrease of fracture parameters such as stress intensity factor [ 101 ] and stress concentration factor [ 102 ], but the supplied voltage increase was only up to 150 V in their studies [ 100 , 103 , 104 ] due to limited voltage. The piezoelectric actuators have the advantage to control/repair the damaged aerospace structures, but it has a limitation of the voltage.…”
Section: Discussion and Critical Reviewsmentioning
confidence: 99%
“…The ideas were developed to produce compression/tension stress around the damaged area along with the width of the piezoelectric actuator. The authors stated that increasing the piezoelectric voltage will result in a decrease of fracture parameters such as stress intensity factor [ 101 ] and stress concentration factor [ 102 ], but the supplied voltage increase was only up to 150 V in their studies [ 100 , 103 , 104 ] due to limited voltage. The piezoelectric actuators have the advantage to control/repair the damaged aerospace structures, but it has a limitation of the voltage.…”
Section: Discussion and Critical Reviewsmentioning
confidence: 99%
“…Sarangi et al 115 experimentally verified the optimal strain gauge locations and their importance in the accurate determination of mode I SIF using daily and Sanford’s single-strain gauge training (DS technique). Abuzaid et al 116 conducted the experimental work for the repair of the damaged plate (edge-cracked) with a bonded PZT actuator. To obtain the SIF for a mode I crack propagation, strain gauges were used.…”
Section: Repair/control Methods In Fracture Mechanics Studiesmentioning
confidence: 99%
“…In the year 2017, a few studies were found on the active repair of metallic structures. For instance, Abuzaid et al ,,, used PZT patches for the repair of the plate through an experimental, numerical, and analytical method since it can be developed for metallic and nonmetallic materials of repair. However, in the next level of study, it can be possible to consider tubes/pipes or other types of structures for active repair because this type of structural repair has been found in passive repair .…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The ideas developed to produce stress (compression/tension) on the stress distribution around the hole and along with the width of the damaged plate by the piezoelectric actuator. The methodologies were adopted via experimental work for an edge-cracked plate [92] and edge-and center-cracked analytical modeling using the crack-closer method [91] and weight function method [92] and numerical simulation via ANSYS simulation [92,93]. To determine SIF for the center-cracked plate, concentrated on the location of the piezoelectric patch on a cracked plate with respect to the dimension by changing the patch location and thickness of adhesive layers.…”
Section: Active Controlmentioning
confidence: 99%